Ensino do direito: o direito como multiplicador de cidadania - Alves Junior, Mauro Gonzaga (2019)
This dissertation aims to analize how little the dogmatic and formal education on Law, in force in Brazil since its creation in 1827, has evolved, when considered the constant transformation of the society. Considering as well that Law is a human phenomenon, including the Natural Rights, generated and exercised by humans. How the teaching of Law could be connected to the current social demands? Could the teaching of Law contribute to consolidate the exercise of citizenship and to decrease contest on peripheral ways? The solid structure of the teaching of Law based on a knowledge which is dogmatic, abstract and frequently divorced of the social context promotes the myth that the juridical system is able to answer all the questions of the society. It is possible to witness the estrangement and lack of preparation of the Law operators in face of complex contemporary social demands. This context has been called “the crisis of the teaching of the Law”, what in fact points to a wider crisis on several fields of knowledge. Considering the key point of this study, the teaching of Law should encourage the (new) bachelor to better exercise his capacity of deep thinking in order to face the social context critically, on a historical perspective, efficiently connecting Law and society, what would reflect in positive consequences to all. This study is reinforced by the ideal of justice pursued by the present society and the new paradigms of efficiency and functionality of the Law. In this scenario, it is required a qualitative advance in the teaching of Law. It is not only enough to change the way of teaching Law, it is necessary to change how Law is seen and learnt, what we believe is done by strengthening and deepening the study of propaedeutic disciplines like Theory of State, Sociology, Philosophy, among others disciplines which have been overridden in the school curriculum. Thus, the Law operator, on a wider and more participative social perspective, become more than a mere litigant agent, a multiplier of citizenship, helping to control the number of disputes in regions of poverty through dialogue and focus on the citizen. The present search is based on theoretical methodology, centred in revision of bibliography. The purpose of changing the paradigm of the teaching of Law implies results that only can be measured at mid and long term, requiring the continuation and amplification of this study. The research is conducted by the deductive method and the research technique applied was bibliographic.